Review of Sorina Chiper’s Book “Discourse Studies In Practice” - Linkevičiūtė, Vilma (Respectus Philologicus, 2021)
The book “Discourse Studies In Practice” is a compilation of articles on discourse, written by S. Chiper over fifteen years and published in Romania and abroad. The research of different topics has been done in the methodological framework of critical discourse analysis (CDA). This book aims at discourse researchers and students, and anyone interested in discourse and intercultural studies.